Editor's note - Sebolai, Kabelo (Journal for Language Teaching, 2025)
<!--StartFragment --> <!--StartFragment --> We are very pleased to publish our second volume (Vol. 59 no. 2) of the Journal for Language Teaching slightly earlier than in recent years. This reflects the editorial team’s ongoing efforts to address submission backlogs and improve publication timelines. Despite challenges in securing reviewers, nine diverse articles were accepted for this issue. <!--EndFragment -->